Lack and accumulation of boron in the leaves after foliar spraying in cabbage and cauliflower plants - Alves, Adriana Ursulino; Prado, Renato de Mello [UNESP]; Gondim, Ancélio Ricardo de Oliveira; Correia, Marcus André Ribeiro; Cecílio Filho, Arthur Bernardes [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
Boron deficiency causes biological damage in brassicas according to the growth phase. In this condition, foliar spraying of B causes immediate effects of nutrient accumulation on leaves that may vary in brassicas but are not known. Therefore, the nutritional deficiency as well as the accumulation of B in the leaves over 30 days after their spraying on cabbage and cauliflower plants were evaluated. Were, two experiments were carried out to evaluate the lack of B in the nutritive solution on the nutrition, growth and production of the two brassicas. The other experiments evaluated the dry mass and B leaf content at 0.12 (3 h); 0.25 (6 h); 0.5 (12 h) 1, 5, 15 and 30 days after leaf spraying of the micronutrient and also in the plants that did not receive B in the two brassicas. The effect of the lack of boron was evident in the final growth stage of the plants, causing a decrease in productivity, cabbage was more sensitive to nutrient deficiency than cauliflower, however. Boron is slowly accumulated by the leaves of the 'Astrus' cabbage, absorbing 50% of the applied B, about 15 days after its application and 'Verona' cauliflower, at three days and 12 hours after its application.
Deficiência e acúmulo de boro nas folhas após a pulverização foliar das plantas de repolho e de couve-flor
Keywords: Brassicas; Micronutrient; Nutrition